2020
DOI: 10.1016/j.ijnss.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-induced aphasia therapy for patients with aphasia: A systematic review

Abstract: Objectives This study aimed to systematically evaluate the effects of constraint-induced aphasia therapy (CIAT) for aphasic patients reported by randomized controlled trials. Methods Relevant randomized controlled trials were retrieved from 11 electronic databases. A methodological quality assessment was conducted in accordance with the Cochrane Handbook, and meta-analyses were performed by using RevMan 5.2. A descriptive analysis was conducted when the included trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Most previous studies of Constraint and Multimodal aphasia therapies for chronic aphasia utilised non-randomised designs or were small phase I or II pilot trials subject to participant selection and other biases 8 9 11–13. These study limitations may account for the differences in findings between COMPARE and those of the preliminary trials that showed significant change in global aphasia severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies of Constraint and Multimodal aphasia therapies for chronic aphasia utilised non-randomised designs or were small phase I or II pilot trials subject to participant selection and other biases 8 9 11–13. These study limitations may account for the differences in findings between COMPARE and those of the preliminary trials that showed significant change in global aphasia severity.…”
Section: Discussionmentioning
confidence: 99%
“…CIAT-Plus and M-MAT are hypothesised to rely on different underlying neural recovery mechanisms and may be differentially effective based on aphasia severity 9 10. Systematic reviews of trials of CIAT-Plus and M-MAT reveal moderate-high effect sizes11–13 but studies are limited by small sample sizes (n<15), inadequate comparator groups, and recruitment and detection bias. Determining the most effective intervention for severity-based and other sub-groups of people with aphasia may lead to improved patient outcomes and reduced healthcare costs.…”
Section: Introductionmentioning
confidence: 99%
“…Aphasia is also a common consequence of stroke, affecting 35% of patients [ 61 ]. In a 2020 systematic review and meta-analysis, there was evidence supporting the use of face-to-face constraint-induced aphasia therapy which focuses on forcing patients to use verbal language with massed practice [ 62 ]. In this review, 6 quasi-experimental studies [ 34 , 36 , 40 , 44 46 ] explored the impact on aphasia using mobile apps built on similar principles to constraint-induced aphasia.…”
Section: Discussionmentioning
confidence: 99%
“…This mirrors research on higher intensity interventions from other areas of stroke, for example, for upper limb movement [6]. Evidence for intensive therapy comes largely from studies aiming to remediate language impairment [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 94%